PENGEMBANGAN EVALUASI MULTIPLE CHOICE MENGGUNAKAN QUIZIZZ PAPER MODE PADA KELAS V TEMA 2 SUBTEMA 2 PENTINGNYA UDARA BERSIH BAGI PERNAPASAN - Resyi Abdul Gani; Tatang Muhajang; Putu Merischa Deabella Aurellia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Development of Multiple Choice Evaluation Using Quizizz Paper Mode in Class V Theme 2 Sub Theme 2 The Importance of Clean Air for Respiration. This research is motivated by the use of less diverse evaluation media which is one of the main factors in the lack of success in the learning evaluation process. This research aims to develop learning evaluation media on theme 2 subtheme 2 the importance of clean air for learning breathing 3. The research method used is Research and Development using the ADDIE model. This research was carried out at SDN Lawanggintung 1 Bogor in class V with the results of the research showing that the quizizz paper mode evaluation media developed had a very feasible category. With media experts at 85% "very worthy", language experts at 97% "very worthy", material experts at 88% "very worthy", evaluation experts at 93% "very worthy", student responses were 95% and teacher responses were 94%. Based on the results of this research, it was concluded that the quizizz paper mode evaluation media developed was very suitable for use as an evaluation media in the classroom.